Cardiovascular diseases in women – impact of the menopausal period - Stachowiak, Grzegorz; Faflik, Urszula; Stetkiewicz, Tomasz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2006)
Cardiovascular diseases (CVD) are the main reason for female morbidity and mortality. Special attention should be paid to ischaemic heart disease, with its sex-dependent epidemiology, clinical image, as well as diagnostic and therapeutic problems. Hormonal and metabolic alterations of the menopausal period negatively influence the state of the circulatory system. Using hormone therapy we modify the risk of CVD, but low oestrogen doses, transdermal route of administration and modern progestogens make this therapy safer for menopausal women.